1998
DOI: 10.1086/452359
|View full text |Cite
|
Sign up to set email alerts
|

Financial Liberalization, Savings, and Economic Development in Pakistan

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. The University of Chicago Press is collaborating with JSTOR to digitize, preserve and extend access to Economic Development and Cultural Change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 5 publications
5
32
0
1
Order By: Relevance
“…We find that the risk premium owing to political risk is very large, lying somewhere between 7.5% and 12%. Khan and Lubna, 2001). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We find that the risk premium owing to political risk is very large, lying somewhere between 7.5% and 12%. Khan and Lubna, 2001). …”
Section: Resultsmentioning
confidence: 99%
“…In 1995, the need was felt for an All Share Index to reconfirm the KSE-100 and also to provide the basis of index trading in futures. The KSE All Share Index was introduced in September 1995 (Khan and Lubna, 2001) 1 .…”
Section: Pakistani Stock Marketmentioning
confidence: 99%
“…Hence, following Khan and Hasan (1998), Laumas (1998) and Pentecost and Moore (2006), it is proxied by the investment to income ratio, I/Y, which is likely to vary directly with the average real return on capital 2 . The models now become:…”
Section: Mckinnon's Complementarity Hypothesismentioning
confidence: 99%
“…For example, DeMelo and Tybout (1986), Edwards (1988) and Morriset (1993) focused on the investment equation, whereas Harris (1979) and Thornton and Poudyal (1990) modelled the demand for money function. The study of Fry (1978), Laumas (1990), Thornton (1990) and Khan and Hasan (1998) tested the complementarity hypothesis by estimating both investment (or savings) and the demand for money functions. Pentecost and Moore (2006) investigated the interdependence between the investment and money legs of the joint hypothesis in a simultaneous system of equations for India.…”
Section: Introcutionmentioning
confidence: 99%
“…Ahmed and Ansari (1995) used price variables as the relevant financial factors for growth in Bangladesh and found weak evidence in support of the McKinnon-Shaw hypothesis. However, Khan and Hasan (1998) in a study for Pakistan found strong support for the "McKinnon-Shaw" hypothesis. An important point worthy of note is the similarity between the structuralists and the repressionists which bothers on the efficient utilization of resources in the pursuit of an economic growth agenda.…”
Section: Introductionmentioning
confidence: 99%